The crisis in psychiatry: A public health perspective. (August 2014) - Pingani, Luca; Luciano, Mario; Sampogna, Gaia; De Rosa, Corrado; Pinna, Federica; Volpe, Umberto; Vecchio, Valeria Del; Fiorillo, Andrea
Abstract The role and responsibilities of psychiatry and psychiatrists have changed significantly in recent decades as a consequence of changes in society. The target of psychiatrists has moved from the treatment of specific mental disorders to the management of a wide range of psychological conditions. Following these changes, a public health approach has been claimed as necessary for psychiatric practice and research, given the current ongoing crisis in mental health. If we want to promote a public health approach, the following actions should be responsibly taken by modern mental health professionals: (1) the identification of causes of mental disorders, (2) the refinement of diagnoses, (3) the social inclusion of patients, (4) the involvement of users and carers in mental health research and practice, and (5) the improvement of psychiatric treatments and services. This crisis should represent a stimulus for all psychiatrists and a reconceptualization of psychiatry as public health is not in question.